Patient outcomes and costs associated with functional medicine-based care in a shared versus individual setting for patients with chronic conditions: a retrospective cohort study. Issue 4 (13th April 2021) - Beidelschies, Michelle; Alejandro-Rodriguez, Marilyn; Guo, Ning; Postan, Anna; Jones, Tawny; Bradley, Elizabeth; Hyman, Mark; Rothberg, Michael B
Abstract : Objective: To compare outcomes and costs associated with functional medicine-based care delivered in a shared medical appointment (SMA) to those delivered through individual appointments. Design: A retrospective cohort study was performed to assess outcomes and cost to deliver care to patients in SMAs and compared with Propensity Score (PS)-matched patients in individual appointments. Setting: A single-centre study performed at Cleveland Clinic Center for Functional Medicine. Participants: A total of 9778 patients were assessed for eligibility and 7323 excluded. The sample included 2455 patients (226 SMAs and 2229 individual appointments) aged ≥18 years who participated in in-person SMAs or individual appointments between 1 March 2017 and 31 December 2019. Patients had a baseline Patient-Reported Outcome Measurement Information System (PROMIS) Global Physical Health (GPH) score and follow-up score at 3 months. Patients were PS-matched 1:1 with 213 per group based on age, sex, race, marital status, income, weight, body mass index, blood pressure (BP), PROMIS score and functional medicine diagnostic category. Primary and secondary outcome measures: The primary outcome was change in PROMIS GPH at 3 months. Secondary outcomes included change in PROMIS Global Mental Health (GMH), biometrics, and cost. Results: Among 213 PS-matched pairs, patients in SMAs exhibited greater improvements at 3 months in PROMIS GPH T-scores (mean difference 1.18 (95% CI 0.14 to 2.22), p=0.03) and PROMIS GMH T-scores (mean difference 1.78 (95% CI 0.66 to 2.89), p=0.002) than patients in individual appointments. SMA patients also experienced greater weight loss (kg) than patients in individual appointments (mean difference −1.4 (95% CI −2.15 to −0.64), p<0.001). Both groups experienced a 5.5 mm Hg improvement in systolic BP. SMAs were also less costly to deliver than individual appointments. Conclusion: SMAs deliver functional medicine-based care that improves outcomes more than care delivered in individual appointments and is less costly to deliver.